2005
DOI: 10.1097/01.alc.0000164361.62346.d6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Oral Self-Administration of Alcohol In ??-Opioid Receptor Knock-Out Mice

Abstract: Our results indicating decreased alcohol consumption, lower saccharin preference, and higher quinine preference in KOR KO mice are in line with previous observations of opioid involvement in maintenance of food intake and raise the possibility that the deficient dynorphin/KOR system affects orosensory reward through central mechanisms which reduce alcohol intake and disrupt tastant responses, either as direct effects of absence of kappa-opioid receptors, or as effects of indirect developmental compensatory cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 57 publications
10
96
4
1
Order By: Relevance
“…36 A complete knockout of OPRK1 significantly reduced alcohol preference and consumption in mice. 39 Alteration of the k-opioid system expression was further investigated in Withdrawal Seizure-Prone (WSP) and Withdrawal Seizure-Resistant (WSR) mice, 68 using in situ hybridization (ISH) and KOR autoradiography. Ethanol withdrawal increased PDYN mRNA in multiple brain regions of WSP, but not WSR mice; 68 basal KOR binding was higher in WSR mice than in WSP mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 A complete knockout of OPRK1 significantly reduced alcohol preference and consumption in mice. 39 Alteration of the k-opioid system expression was further investigated in Withdrawal Seizure-Prone (WSP) and Withdrawal Seizure-Resistant (WSR) mice, 68 using in situ hybridization (ISH) and KOR autoradiography. Ethanol withdrawal increased PDYN mRNA in multiple brain regions of WSP, but not WSR mice; 68 basal KOR binding was higher in WSR mice than in WSP mice.…”
Section: Discussionmentioning
confidence: 99%
“…38 OPRK1 knockout mice demonstrate an increased ethanol-evoked dopamine response in the nucleus accumbens 37 and show less oral alcohol self-administration than wild-type mice. 39 The OPRK1 gene is located on human chromosome 8. The 22 kb OPRK1 gene contains four exons, including a newly identified exon that encodes the 5 0 untranslated region.…”
Section: Introductionmentioning
confidence: 99%
“…A similar relationship may also exist with the drinking of ethanol. There is evidence that ethanol intake is stimulated by peripheral injection of opioid agonists, and it is decreased by an opioid receptor antagonist (Hubbell et al, 1986;Messiha, 1989;Oswald and Wand, 2004) or by deletion of the k-opioid receptor gene (Kovacs et al, 2005). Also, 2 recent studies from our laboratories show that PVN or i.c.v.…”
Section: Functional Consequences Of Increased Peptide Expressionmentioning
confidence: 96%
“…The results of this gene-mapping study suggested that genetic polymorphisms in kappa opioid receptors may contribute to genetic predisposition to voluntary alcohol-drinking behavior. Our follow-up studies on opioid receptor kappa 1 knock-out mice indicated that complete constitutional dysfunction of the Oprk1 gene can reduce alcohol consumption (20), however chromosome position of microsatellite marker " D1Mit167" in the MIT database was assigned incorrectly, and the proposed chr. 1 region was not associated with genetic variation in alcohol consumption (21).…”
Section: Introductionmentioning
confidence: 94%